Occurrence of diazotrophic bacteria and arbuscular mycorrhizal fungi on the cassava crop - Balota, Elcio Liborio; Lopes, Eli Sidney; Hungria, Mariangela; Dobereiner, Johanna (Pesquisa Agropecuaria Brasileira, 1999)
This study was performed to evaluate the occurrence and to isolate and identify diazotrophic bacteria and arbuscular mycorrhizal fungi associated with the cassava (Manihot esculenta) crop. Samples from rhizospherical soil, roots, tubers, stems and leaves from several localities of the States of Rio de Janeiro, São Paulo and Paraná, in Brazil, were inoculated in three media specific for diazotrophic associative bacteria, LGI-P, NFb-malate and NFb-GOC, evaluating the most probable number of cells and the acetylene-reducing activity. Diazotrophic bacteria were detected in all plant parts except for the leaves, and were identified as Klebsiella sp., Azospirillum lipoferum and a bacterium called "E", probably belonging to the Burkholderia genus. Bacterium E was able to accumulate, in the N-free semi-solid media, from 7.63 to 14.84 mg of N/g of C and to maintain N fixation capacity after ten consecutive transferences. Mycorrhizal root colonization varied from 31% to 69% and spore density from 10 to 384 spores/100 mL of soil, predominating the species Entrophospora colombiana and Acaulospora scrobiculata in Rio de Janeiro, A. scrobiculata and Scutellospora heterogama in Paraná and in Piracicaba (São Paulo), and A. appendicula and S. pellucida in Campinas (São Paulo).